Online Education in Times of the Pandemic: A Quantitative Study of the Learning Experiences Among Filipino Pre-Service Language Teachers - Catherine Jean A. Brillantes (International Journal on Integrated Education, 2022)
The upsurge in Covid-19 cases was marked as the greatest malady of the educational sector, which forced the academic institutions across the globe to shift towards the internet-based distance education, regardless of the readiness of both the learners and the instructors alike to adapt to the new learning modality. More than a year has elapsed since the emergence of the pandemic, yet the online learning experiences of Filipino pre-service teachers remains largely a mystery. This study attempts to investigate the learning experiences of 91 Filipino pre-service teachers, particularly those who majored in English, with the use of the College Student Learning Experience Survey (CSLES), an online survey developed by Zhang and Zhou (2021). The results revealed that the pre-service teachers were able to have positive learning experiences in their online classes. This is evident in the high level of learning satisfaction of the respondents, and their positive view of their learning communities and perceived student support. It was also reported that majority of the prospective teachers experienced symptoms of anxiety and depression in their online classes. Moreover, internet connectivity issues, power outages and poor learning environment were listed as major concerns that the prospective teachers endured in their virtual class sessions. Finally, a relationship between the universities in which the respondents were enrolled in and their perceived student support and learning satisfaction was also found. The year level of the respondents was also found to have a significant effect on their overall learning process and perception of learning community.